2015
DOI: 10.3791/52560
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Ablation of Atrial Fibrillation

Abstract: Background: Pulmonary vein isolation (PVI) is an established treatment for atrial fibrillation (AF). During PVI an electrical conduction block between pulmonary vein (PV) and left atrium (LA) is created. This conduction block prevents AF, which is triggered by irregular electric activity originating from the PV. However, transmural atrial lesions are required which can be challenging. Re-conduction and AF recurrence occur in 20 -40% of the cases. Robotic catheter systems aim to improve catheter steerability. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…All manual and robotic procedures were performed using a Thermocool ® SmartTouch ® ablation catheter (STc) (Biosense Webster Inc., Diamond Bar, California). The Amigo system, which has been previously described in detail [8] , [12] , consists of a robotic arm mounted on the rails at the foot of the procedure table and a remote controller connected to the robotic arm via a cable [ Fig. 1 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All manual and robotic procedures were performed using a Thermocool ® SmartTouch ® ablation catheter (STc) (Biosense Webster Inc., Diamond Bar, California). The Amigo system, which has been previously described in detail [8] , [12] , consists of a robotic arm mounted on the rails at the foot of the procedure table and a remote controller connected to the robotic arm via a cable [ Fig. 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Amigo ® Remote Catheter System (Catheter Precision Inc., Ledgewood, NJ, USA) is a relatively new robotic (electromechanical) system for catheter navigation that allows the use of standard catheters and sheaths. Previously published studies, using the system for a variety of electrophysiologic procedures, have reported good results in terms of efficacy and safety [8] , [9] , [10] , [11] , [12] . The present study is the first designed to use a force-sensing catheter to compare force-related parameters during atrial fibrillation ablation using the Amigo robotic system vs. manual catheter manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the arrhythmia was believed to be located at the crista terminalis or superior vena cava. A Schwartz Right 0 sheath, which is used to stabilize the catheter, achieved successful ablation, with a contact force of 10 to 20 g and ablation at 30 Watts [ 26 , 31 ]. Non-fluoroscopic ablations can be achieved with intracardiac echocardiography to locate the structures in Koch's triangle.…”
Section: Reviewmentioning
confidence: 99%
“…This may be due to its large instrumental dimension needed for entry port sites. 16 Robotics not only has its role in cardio-surgeries but acts as an upheaval for cardiologists to intervene in their clinical scenarios using Cor Path 200 robot system. It has a remote interventional cockpit and bedside disposable cassette for conducting percutaneous coronary intervention.…”
Section: Robotics In Cardiologymentioning
confidence: 99%